Transporte de volume e calor pelos vórtices da corrente norte do Brasil - Bueno, Luana Ferraz (2018)
A methodology that combines a 24-year long (January 1993 to December 2016) global dataset of eddy trajectories (CHELTON et al., 2011), derived from altimetry, with vertical temperature (T) and salinity (S) profiles from EN4.2.0 dataset (GOOD et al., 2013), derived from XBTs/MBTs, CTDs and Argo floats, was used to reconstruct the mean vertical structure of North Brazil Current (NBC) rings, and to calculate some of their properties. The annual-mean formation of NBC rings was estimated in 6.4 ± 1.8. High inter-annual variability was observed, with 2 to 10 rings being shed at different years. A total of 1466 (698) T (S) profiles were used in order to reconstruct the mean-ring vertical structure. The meridional volume transport of the mean-ring was estimated in 1.3 Sv (1Sv = 106 m3 s −1 ), leading to a annualized transport of 8.3 ± 2.3 Sv. According to these estimates, the NBC rings are responsible for 64% of the northward transport by the upper limb of the Atlantic Meridional Overturning Circulation (AMOC), reaching 80% in years of maximum ring formation. The mean NBC ring showed a maximum T (S) anomaly of 5.7◦C (0.6), at depths of ∼150 (180) m. The contribution of NBC rings was estimated in approximately 40% of the total meridional heat transport across 11◦N.